Philosophy for Education Assistance. On the Constructivist Foundations of Language Teaching - Cyzman, Marzenna (Hybris, 2019)
The aim of the article is to reflect on the philosophical foundations of foreign language teaching on the example of teaching Polish as a foreign language. The starting point of the considerations is the constructivist epistemology (mainly radical constructivist by Ernst von Glasersfeld) and the notion of language / language behavior (languaging - formulated by the biologist and constructivist Humbert Maturana). I am arguing that the teaching of language behavior / orienting behaviour should be an integral part of the didactic process. Language is a much more complex phenomenon, and understood as linguistic behavior refers to emotions, bodily reactions, conventions adopted in a given interpretation community, and the areas of consensual domain we achieve during communication with our interlocutors. Although the constructivist approach is known in the world, it can be observed that the practice of teaching is still dominated by the belief about the passive transmission of knowledge. The constructivist perspective applied to the organization of the didactic process may have practical consequences for formulating certification rules or organization of work during the lesson.